Sex, Race, and Age: Double Discrimination in Torts And Taxes - Mark J. Wolff (Washington University Law Quarterly, 2000)
This Article first provides the traditional scholarly survey of legislative history, statutory analysis, and governmental and judicial interpretations. Part II reviews the history of § 104(a)(2) and offers a substantive inquiry into the Supreme Court opinions in United States v. Burke, Commissioner v. Schleier, and in the major cases leading up to these decisions. Part III then reviews the tax policy assumptions supporting § 104(a)(2) from a perspective of both before and after the 1996 amendments. Part IV chronicles the history and current status of various federally enacted civil rights statutes. This part then presents a historical overview of the emergence of tort reform at the federal and state levels— a reform in many ways diametrically opposed to that of civil rights legislation evolving and expanding the scope of protections and remedies. These two movements— civil rights and tort reform— elucidate the current status of § 104(a)(2). With respect to § 104(a)(2), tort reform takes place not in the traditional sense, Congress passing federal tort reform, but rather through the “back door”— tort reform in a taxing statute. Part V criticizes the judicial craftsmanship used in United States v. Burke and Commissioner v. Schleier. Part VI archives the well-documented negative psychological, physical, social, economical, and societal consequences that result from various forms of discrimination. Part VII applies psychoanalytic and cognitive theories of psychology to support the thesis that the 1996 amendment to § 104(a)(2) is a product of unconscious judicial and legislative discrimination. Finally, Part VIII concludes the Article, recommending that Congress take immediate action to remedy the tax discrimination leveled against victims of dignatory torts and raise revenues to support the exclusion by disallowing deductions for amounts paid to victims of discrimination by the tortfeasors. In an effort to effectively influence the drafting of appropriate legislation, this Article will conclusively demonstrate that in the context of § 104(a)(2) there are no sustainable or well-founded tax or social policy justifications for treating victims of nonphysical injuries differently from those of physical injuries. Rather, broad social and congressional policy requires that victims of discrimination, in all its forms, be treated equally for tax purposes.
Keywords: Personal injuries; Income tax exemptions; Race discrimination; Sex discrimination; Age discrimination; Damages (Law)